Desa Tangguh Ekonomi Dan Kesehatan: Sosialisasi Aplikasi JAMRIDE Terhadap Usaha Mikro, Kecil Dan Menengah - Sholichin; Mayusef Sukmana; Syahrun; Ruminem; Rita Puspa Sari; Dwi Nopriyanto; Anik Puji Rahayu (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2023)
Various advances in various fields have occurred to date, these advances encourage people to continue to innovate. One of the advances that occurred in Penajam Paser Utara Regency was in the field of transportation. The progress that has occurred can be seen with the Jamride application (Penajam Ride) initiated by Penajam young people. However, based on conditions in the field, there are still many Usaha Mikro Kecil dan Menengah (UMKM) who do not know and understand the benefits of joining as a partner of the application. Based on these considerations, it was initiated to carry out socialization regarding applications in Nenang sub-district. In addition, in order to increase brand value for the general public and UMKM in the region, a business logo design training webinar and a tutorial module for loggingo were also conducted, in the field of education and literacy, a reading corner activity was also created with the aim of increasing reading interest in children, besides that a video was made Education about anti-hoax campaigns and coaching videos in drug-prone areas. Jalso carried out other work programs on the environment, namely the implementation of community service work in the environment around the river and the installation of banners and videos appealing to protect the land and water environment, and educational videos on the use of narrow land as agricultural land with verticulture techniques for local residents